Internal and External Factors Affecting Children's Second Language Acquisition - Ngadjen, Syahdania Aini (Huele: Journal of Applied Linguistics, Literature and Culture, 2023)
Second Language Acquisition (SLA) in children is a complex interplay of internal and external factors that significantly influence learning outcomes. This study explores the multifaceted nature of SLA, emphasizing critical variables such as motivation, cognitive abilities, personality traits, age, and emotional states. External determinants, including instructional quality, sociocultural context, and family involvement, are also highlighted. Employing a library research methodology, the study synthesizes insights from diverse academic resources to identify how these factors collectively shape language acquisition trajectories. Findings underscore the dynamic interdependence of internal and external influences, emphasizing tailored instructional strategies and the importance of supportive learning environments. The implications extend to pedagogical practices, parental engagement, and the integration of sociocultural elements to foster effective SLA. The study concludes with recommendations for future research to empirically validate theoretical models and explore innovative approaches in language education.